Inhabiting the diasporic habitus: on Stuart Hall's Familiar Stranger: A Life Between Two Islands. Issue 1 (2nd January 2018) - Ang, Ien
ABSTRACT: This reading of Stuart Hall's memoir Familiar Stranger highlights the connection between Hall's unique intellectual voice with the historical specificity of his personal experience as a diasporic subject, growing up at the cusp of the moment of decolonisation, before the solidification of what we now call 'identity politics'.